(untitled) (Contemporary Journal of Social Science Review, 2025)
Second, this research probes into how Snapchat filters impact the views of young beauty while contemporary beauty standards come into play with fast technological innovation in Lahore, Pakistan. A quantitative cross-sectional approach was used to evaluate how filter use can influence beauty standards and self-esteem among 200 18–25-year-olds. Sharing images and confidence in doing so is encouraged by filters, despite a lower satisfaction with a natural look. However, cultural considerations are involved in this association, since Snapchat filters are somewhat consistent with the Pakistani beauty standards. Fewer gender disparities were expected, suggesting that there was a gender-wide influence. Because this suggests that cultural norms are intertwined with the digital beauty technology, mental health practitioners, educators, and social media platforms should develop culturally appropriate treatments to address the entangled relationship between the two.